THE EFFECT OF MANAGERIAL OVERCONFIDENCE ON CORPORATE FINANCING DECISION - Eujenita Siswoyo; Putu Anom Mahadwartha; Bertha Silvia Sutejo (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2015)
The objective of this research is to examine the effect of managerial overconfidence on corporate financing decision of the miscellaneous industry sector in Indonesian Stock Exchange for the period of 2011-2015. This research uses quantitative perspective with linier regression in a panel data for all of the research’s observation. Fixed effect models (FEM) is employed to examine the effect of managerial overconfidence on corporate financing decision. CEO personal characteristics such as profile photo, education, experience, gender, tenure, and age are used as the proxy of managerial overconfidence. The result of this research indicate that: first, CEO overconfidence has positive significant effect on corporate financing decision; second, CEO profile photo has negative significant effect on leverage; third, CEO education has no significant effect on leverage; fourth, CEO experience has positive significant effect on leverage; fifth, male CEO tend to use more debt than female CEO which means gender has positive significant effect on leverage; sixth, CEO tenure has positive significant effect on leverage; seventh CEO age has negative significant effect on leverage.